Penerapan Etika PNS Dalam Pelaksanaan Tugas Aparatur Pelayanan Publik (Suatu Studi di Kantor Camat Wanea Kota Manado) - Santiarsti, Thea; Dengo, Salmin; Ruru, Joorie (Sam Ratulangi University, 2015)
Abstract: Government Regulation 42 of 2004 on Life Coaching Corps and the Code of Conduct for civil servants, explicitly and clearly stated ethical obligation for civil servants in carrying out official duties. But in reality there is still the attitude and behavior of civil servants that do not fit. This research is to answer the question